The Green-Spore Poison Parasol Mushroom, Chlorophyllum molybdites - Lisbeth Espinoza; Matthew E. Smith (EDIS)
The “false parasol” or “green-spored parasol” mushroom (Chlorophyllum molybdites) is a poisonous mushroom that is the most common cause of mushroom poisoning in the United States. This mushroom is widely distributed throughout Florida and the southeastern United States. It commonly creates a complete or incomplete “fairy ring” in lawns, grassy areas, and open woods. When mature, the green-spored parasol mushroom has a large cap, a ring around its stem, and a greenish color on the underside of its gills. This four-page fact sheet describes the morphology, ecology, and distribution of the green-spored mushroom as well as its toxicology and how to treat poisoning from this mushroom. Written by Lisbeth Espinoza and Matthew E. Smith, and published by the Plant Pathology department, January 2016.